1/f noise spectroscopy and noise tailoring of nanoelectronic devices. Issue 4 (6th October 2021) - Balogh, Zoltán; Mezei, Gréta; Pósa, László; Sánta, Botond; Magyarkuti, András; Halbritter, András
Abstract: In this paper, we review the 1/ f -type noise properties of nanoelectronic devices focusing on three demonstrative platforms: resistive switching memories, graphene nanogaps and single-molecule nanowires. The functionality of such ultrasmall devices is confined to an extremely small volume, where bulk considerations on the noise lose their validity: the relative contribution of a fluctuator heavily depends on its distance from the device bottleneck, and the noise characteristics are sensitive to the nanometer-scale device geometry and details of the mostly non-classical transport mechanism. All these are reflected by a highly system-specific dependence of the noise properties on the active device volume (and the related device resistance), the frequency, or the applied voltage. Accordingly, 1/ f -type noise measurements serve as a rich fingerprint of the relevant transport and noise-generating mechanisms in the studied nanoelectronic systems. Finally, we demonstrate that not only the fundamental understanding and the targeted noise suppression is fueled by the 1/ f -type noise analysis, but novel probabilistic computing hardware platforms heavily seek well tailorable nanoelectric noise sources.